THE RELATIONSHIP BETWEEN HOPE AND HARDINESS ON CAREER ADAPTABILITY - Nurfatmah (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2025)
The objective of the present study was to elucidate the relationship between hope and hardiness, and career adaptability in students at SMK Negeri 1 Selong.A quantitative approach was adopted, utilising a correlational method and a measuring instrument comprising three scales: the hope scale, the hardiness scale, and the career adaptability scale.The population of the study comprised 100 students from SMK Negeri 1 Selong. The study's sample size was determined using the simple random sampling technique, with 72 students selected for participation.The collected data underwent a rigorous analysis using multiple linear regression, facilitated by SPSS version 22. The partial test between the hope variable and career adaptability yielded a t-value of 4.642 with a significance level of <0.05, thereby indicating a statistically significant correlation. A similar outcome was observed for the partial test between the hardiness variable and career adaptability, which obtained a t-value of 4.062 with a significance of <0.05, thus confirming a correlation.The simultaneous test between the variables hope and hardiness on career adaptability yielded a t-score of 45,881 with a significance of <0.05, thereby confirming a correlation. The findings of this study indicated a positive relationship between hope and hardiness and career adaptability, suggesting that individuals who possess strong feelings of hope and hardiness tend to exhibit greater adaptability in their professional careers. Conversely, individuals with lower levels of hope and hardiness demonstrate a diminished capacity to adapt to professional challenges